Subjective cognitive decline is associated with a higher risk of objective cognitive decline: A cross-sectional and longitudinal study - Li, Wei; Yue, Ling; Xiao, Shifu (Frontiers in Psychiatry, 2022)
Abstract Background Subjective cognitive decline (SCD) is considered as an independent risk factor for objective cognitive impairment, such as dementia and mild cognitive impairment (MCI), but the mechanism is unclear. Methods The current study consisted of two cohorts, the first of which included 1010 older adults with SCD and 535 normal controls and was followed for 1 year. The second cohort included 94 older adults with SCD and 64 healthy controls. Unlike the first cohort, subjects in the second cohort underwent magnetic resonance imaging and had more detailed neuropsychological tests, such as Mini- mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Digit Span, Auditory Verbal Learning Test (AVLT), Associative Learning Test (ALT), Verbal Fluency (VF), Wechsler’s filling and Wechsler’s building blocks. Results In cohort 1, we found that SCD had a higher risk of objective cognitive impairment compared to normal controls (X2=20.354, p=0.002), and the results of Cox Regression analysis also suggest that SCD was a risk factor for objective cognitive decline (p<0.001, HR=2.412, 95%CI: 1.636~3.558). In cohort 2, we found that the scores of MoCA, digit span, verbal fluency, and Wechsler’s filling of SCD elderly were significantly lower than those of normal controls, but the cortical thickness of the rostral middle frontal gyrus (RMFG) was significantly higher than that of normal controls (p<0.05). Conclusions SCD is a cognition-related disease with multi-cognitive domain impairment, which is associated with a higher risk of objective cognitive impairment. Moreover, the increased cortical thickness of the left rostral middle frontal gyrus (RMFG) might be an important mechanism of cognitive decline in SCD. Keywords SCD, RMFG, Cognition, MRI, cohorts